Propuesta de inclusión de indicadores financieros al análisis de los estados financieros en el área de financial controllership (2020)
This project was carried out for the Financial Controllership (FC) area of ​​Enterprise Operations Bogotá (EOB), in charge of controlling the Financial Statements and reviewing the reliability of the reported numbers. EOB functions as a financial service center for Diageo companies around the world. This project focuses on the market made up of Paraguay, Uruguay and Brazil, also known as PUB. It arose as a result of the opportunity identified in the DOFA analysis to implement an additional tool, such as financial ratios, to the Financial Statements analysis. This, due to the fact that the analysis is currently carried out only horizontally, comparing the variations of the period in question compared to the previous month and year. A mixed methodology was used: qualitative and quantitative. The latter to answer the question of which financial indicators could be implemented in the area of ​​FC PUB to carry out a more complete analysis of the Financial Statements. Through the literature review, there were identified sets of indicators that when implemented, were useful for: 1) benchmarking the company's position vis-à-vis the industry, 2) evaluating efficiency and 3) performance, and giving warning signs that would allow the prevention of the 4) commercial and financial crisis, and the 5) bankruptcy. Through validation with the FC team, it was concluded that the most useful and relevant indicators for the area are those that measure liquidity, evaluate efficiency and performance, and provide relevant insights for crisis prevention. The eleven indicators proposed were: Acid Test, Current Ratio, Cash Ratio, Defensive Interval Ratio, Financial Stability Ratio, Working Capital to Total Assets, ROA, ROE, Asset Turnover Ratio, Debt to Assets and finally Debt to Equity.